Literacy-Based Project Based Learning (PjBL) in Fiqh Learning at MAN 1 Lamongan - Hepi Ikmal; Nurul Afifah (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2023)
This study discusses the implementation of the literacy-based Project Based Learning (PjBL) learning model in Jurisprudence learning in MAN 1 Lamongan using a case study qualitative approach and data collection through interviews, observation, and documentation. The result of this research is that the teacher assigns students to work on a project in the form of papers and videos, where when assigning students using this PjBL model, the steps of the PjBL model are also applied. Among them are questions. This step questions are carried out by asking basic questions students. Planning is done by grouping students and determining what is in the project. Scheduling determines the project completion time. Supervision is carried out by monitoring the project work process. The assessment was carried out by students presenting the results of the project. Evaluation, by reflecting between the teacher and students.